2019
DOI: 10.1007/s11269-019-02342-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Water-Level Forecasting Using Dilated Causal Convolutional Neural Networks

Abstract: Accurate forecasts of hourly water levels during typhoons are crucial to disaster emergency response. To mitigate flood damage, the development of a water-level forecasting model has played an essential role. We propose a model based on a dilated causal convolutional neural network (DCCNN) that can yield water-level forecasts with lead times of 1-to 6-h. A DCCNN model can efficiently exploit a broad-range history. Residual and skip connections are also applied throughout the network to enable training of deepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…where t is the current time, ∆t is the lead time,Ĥ t+∆t is the forecasted river stage at time t + ∆t, L denotes the lag length of the input variables, R t−L is the antecedent rainfall at time t − L, H t−L is the antecedent river stage at time t-L, and S t−L is the antecedent tidal level at time t − L. Following the approach adopted by Wang et al [45], the lag length was set as 6 h in the present study; this lag length takes into consideration the concentration time of a watershed. To investigate the lead time, the lead time commonly applied in hydrology modeling of 1-6 h was used in this study [45][46][47].…”
Section: Methodology 21 Data-driven Model For River Stage Forecastingmentioning
confidence: 99%
“…where t is the current time, ∆t is the lead time,Ĥ t+∆t is the forecasted river stage at time t + ∆t, L denotes the lag length of the input variables, R t−L is the antecedent rainfall at time t − L, H t−L is the antecedent river stage at time t-L, and S t−L is the antecedent tidal level at time t − L. Following the approach adopted by Wang et al [45], the lag length was set as 6 h in the present study; this lag length takes into consideration the concentration time of a watershed. To investigate the lead time, the lead time commonly applied in hydrology modeling of 1-6 h was used in this study [45][46][47].…”
Section: Methodology 21 Data-driven Model For River Stage Forecastingmentioning
confidence: 99%
“…Khac-Tien [16] combines the neural network with a fuzzy inference system for daily water levels forecasting. Other authors [31,34] apply the neural network model to predict flood with collected gauge measurements. Those models, implementing neural network models for one dimension, did not take into account the spatial correlations.…”
Section: Related Workmentioning
confidence: 99%
“…The ratio of training data to testing data is about 2 to 1 (a total of 1265 and 560). To further evaluate the prediction performance of the NN-based models, the root mean square error (RMSE) [38], mean absolute error (MAE) [39], determination coefficient (R 2 ) [38], and coefficient of efficiency (CE) [39] were applied to this research, which indicates the discrepancy between observed and forecasted air-conditioning electricity consumption. RMSE and MAE represent the errors between two sets of data; meanwhile, R 2 , and CE represent the consistency between the observed and predicted air-conditioning electricity, and the greater the consistency, the better the results.…”
Section: Model Constructing and Data Processingmentioning
confidence: 99%